2017
DOI: 10.1007/s11046-017-0191-z
|View full text |Cite
|
Sign up to set email alerts
|

A Twenty-First-Century Perspective of Disseminated Histoplasmosis in India: Literature Review and Retrospective Analysis of Published and Unpublished Cases at a Tertiary Care Hospital in North India

Abstract: Disseminated histoplasmosis is being increasingly recognized in India. There is a need to undertake well-designed, analytical studies utilizing appropriate diagnostic modalities to understand the epidemiology of this neglected disease in proper perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 58 publications
4
40
1
Order By: Relevance
“…The high rate of HIV-infected patients found in this study is in agreement with data from other Latin American countries (Arango et al, 2011;Vantilcke et al, 2014), Asia (Gupta et al, 2017), and Europe (Antinori et al, 2006), demonstrating the strong relationship between HIV and histoplasmosis co-infection.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The high rate of HIV-infected patients found in this study is in agreement with data from other Latin American countries (Arango et al, 2011;Vantilcke et al, 2014), Asia (Gupta et al, 2017), and Europe (Antinori et al, 2006), demonstrating the strong relationship between HIV and histoplasmosis co-infection.…”
Section: Discussionsupporting
confidence: 93%
“…A significant increase was observed from the 1980s onwards, after the rise in HIV/AIDS cases, mainly of the disseminated form, giving histoplasmosis a prominent place among fungal diseases seen in this country (Ferreira and Borges, 2009). This study revealed a high incidence of histoplasmosis in middle-aged persons and a predominance of the disease among males, factors that were also observed in studies conducted in China, India, and Panama (Gutierrez et al, 2005;Pan et al, 2013;Gupta et al, 2017). The male predominance can be explained by the fact that HIV is more prevalent in males than females in Brazil (Damasceno et al, 2013).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The soil of the Ganges River has been shown to harbour spores of H capsulatum . Due to reasons which are currently unclear, the last 15 years have seen a sharp increase in case reports and small series of patients with PDH from different parts of India . This includes patients from regions previously not known to be endemic for the disorder .…”
Section: Introductionmentioning
confidence: 99%
“…Due to reasons which are currently unclear, the last 15 years have seen a sharp increase in case reports and small series of patients with PDH from different parts of India . This includes patients from regions previously not known to be endemic for the disorder . In a recent study of 37 Indian patients with PDH, adrenal involvement was common, being reported in 38% of subjects…”
Section: Introductionmentioning
confidence: 99%